Study on a Mathematical Model of the Vibration Transmission Path of Multistage Transmission Gearboxes - Kong Zhaoyi; Li Fan (Jixie chuandong)
Aiming at the existence of multiple complex vibration transmission paths in the multistage transmission gearbox, a mathematical model of the multistage transmission vibration transmission path of the gearbox is established, and the frequency spectrum structure of the vibration model is deduced by the Fourier series analysis method. Vibration source, time-varying transmission path and multistage transmission gear vibration frequency characteristics are considered comprehensively, an equivalent time-varying transmission path function from the meshing point to the accelerometer mounted on the ring tooth is proposed and the time-varying transmission path is modeled as having different periodic function of decay amplitude. Taking the multistage transmission gearbox as an example, the validity of the proposed mathematical model is verified by simulation and experiment. The model can provide reference for the condition monitoring and fault diagnosis of the multistage gearbox.